A arte do disfarce: a maquiagem como mídia e o processo de construção de personagens na obra audiovisual - Pinheiro, Micheline Penafort (2016)
Our subject of study in this Master's thesis is the process of characterization of characters in the audiovisual work. Therefore, we selected two characters: Dorothy Benson Brazilian novel Geração Brasil (2014), and the movie fan Açaí com Jabá (2002) a short film of paraense production done in film. In terms of methodology, the survey combined the practical experience of the author as a make-up artist to the theoretical foundations about creating processes (Leão and Salles), communication through cyberspace networks (Leão), the technical function in audiovisual production (Rodrigues), cultural semiotics (Ferreira) and history of makeup (Leite). In addition to these characters, the corpus of the research brought together the various types of makeup techniques and speeches on social networks like Youtube, Facebook, Instagram, Snapchat, some blogs, among them some professionals who called our attention in his poetic. Within this interrelationship considered the makeup as part of a multilinear set a device (Deleuze), using the account of the experience in function and concept mapping (Leão) to propose, as expected result, a type of makeup, their practices and information, as well as the cultural context in which the character is inserted in the audiovisual plot